دور المرآة الفلسطينية في تعزيز وظائف التربية الأسرية لدى أبنائها كما وردت في السنة النبوية - الجمل، محمد كامل (جامعة عمان العربية - عمادة البحث العلمي والدراسات العليا, 2021)
هدفت الدراسة إلى إبراز دور المرأة الفلسطينية في تعزيز وظائف التربية الأسرية لدى أبنائها كما وردت في السنة النبوية، وقد استخدم الباحث المنهج الوصفي التحليلي، وقد تناولت الدراسة جملة من وظائف التربية الأسرية للمرأة الفلسطينية، كما وردت في السنة النبوية. وقد توصلت الدراسة إلى نتائج أهمها: تأصيل وظائف التربية الأسرية في ضوء السنة النبوية: الإيمانية، الأمنية، الاجتماعية، الخلقية، التعليمية، الاقتصادية، الجهادية، وجود دور بارز للمرأة الفلسطينية في التربية الأسرية لدى أبنائها كما وردت في السنة النبوية، من خلال النتائج يوصي الباحث بما يلي: ضرورة الاهتمام بسنة النبي صلى الله عليه وسلم في إبراز دور المرأة في التربية الأسرية في حياة الصحابة والصحابيات.
The aim of the research is to highlight the role of Palestinian women in enhancing family education functions for their children as they appeared in the prophetic year, and the researcher used the descriptive analytical approach, and the research dealt with a number of family education functions as mentioned in the prophetic year, which are as follows: The research has reached results The most important: Establishing family education jobs in the light of the Prophet's Sunnah: security, faith, social, moral, educational, economic, jihadism, and the presence of a prominent role for Palestinian women in family education for their children as mentioned in the Prophet's year, through the results the researcher recommends the following: the necessity Paying attention to the Sunnah of the Prophet (may God bless him and grant him peace) in highlighting the role of women in family education in the companions and companions neighborhood.
Keywords: التنشئة الاجتماعية -- المرآة الفلسطينية -- التربية الوالدية -- تربية الناشئة -- القيم الإسلامية